DINAMIKA PASAR KAKAO INTERNASIONAL: DAMPAK EKONOMI PADA PRODUKSI KAKAO DOMESTIK, HARGA DUNIA, INFLASI, DAN HARGA LOKAL - Rezka, Rezka Yoli Amanda; Tan, Firwan; Putra, Febriandi Prima (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This study explores the dynamics of the international cocoa market and its impact on Indonesian cocoa exports by focusing on economic factors such as domestic production, world prices, inflation, and local prices. The main findings show that for cocoa exports to Malaysia, cocoa production and world cocoa prices have a positive and significant influence on export volumes, where an increase in production and world prices increases exports and strengthens bilateral trade. In contrast, domestic inflation shows no significant effect, while local prices have a significant negative impact, reducing exports as producers prefer the domestic market. In the context of exports to India, cocoa production showed no significant effect, due to a mismatch between increased production and international demand or quality and infrastructure issues. World cocoa prices are also insignificant, while local prices are positive and significant, encouraging producers to increase exports to maximize profits. For exports to the United States, cocoa production is positive and significant, reflecting strong demand from the US market. World cocoa prices have no significant effect, suggesting that other factors such as quality and trade policy determine export volumes more. Inflation is positive and significant, encouraging producers to focus on international markets as a way to coordinate exports.